HEMOGLOBIN H DISEASE AND GROWTH: A COMPARATIVE STUDY OF DHbH AND NDHbH PATIENTS - Hunnuan, Issanun; SAnpakit, Kleebsabai; Lertbannaphong, Ornsuda; Buaboonnam, Jassada (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Hemoglobin H disease (HbH), a hemoglobinopathy resulting from abnormal alpha globin genes, is classified into two categories: deletional HbH (DHbH) and non-deletional HbH (NDHbH). The alpha-mutation genotypes exhibit a range of clinical anemias, which differentially impact patient growth. Objectives: This retrospective study assessed the growth of HbH patients at Siriraj Hospital, Mahidol University. Methods: Patients diagnosed with HbH between January 2005 and April 2021 were analyzed using growth standard scores of the Thai Society for Pediatric Endocrinology (2022 version) and BMI-for-age Z scores of the World Health Organization. Growth failure was defined as a patient’s height for age exceeding two standard deviations below the mean. Results: Of the 145 HbH patients, 75 (51.7%) had NDHbH, with –SEA/αCSα being the most common genotype (70 patients; 93.3%). The mean baseline hemoglobin level was significantly lower in NDHbH patients than in DHbH patients (8.16 ± 0.93 g/dL vs. 9.51 ± 0.68 g/dL; P < 0.001). Splenomegaly and growth failure prevalences were higher in NDHbH patients (37.3% vs. 0%, with P < 0.001, and 22.7% vs. 8.6%, with P = 0.020, respectively). Multivariable analysis revealed that splenomegaly > 3 cm was associated with growth failure (OR = 4.28; 95% CI, 1.19–15.39; P = 0.026). Conclusions: NDHbH patients exhibited lower hemoglobin levels and more pronounced splenomegaly than DHbH patients. Growth failure can occur in both HbH types but appears more prevalent in NDHbH. Close monitoring of growth velocity is essential, and early treatment interventions may be required to prevent growth failure.